Potential for Deep Rural Broadband Coverage With Terrestrial and Non-Terrestrial Radio Networks - Feltrin, Luca; Jaldén, Niklas; Trojer, Elmar; Wikström, Gustav (Frontiers in Communications and Networks, 2021)
Since the first generation of cellular networks was rolled out, the priority has been to improve the connectivity and capacity of densely populated areas, such as urban centers, whereas rural areas received less attention. The lower subscriber density of such areas makes it difficult to get a positive business case with current wireless technologies and current cost structures. Base stations are deployed more sparsely in rural areas and are typically shared by several operators and are thus not able to provide high-performance connectivity, compared to urban areas, resulting in a connectivity gap. Third Generation Partnership Project (3GPP) is currently introducing Non-Terrestrial Networks (NTN) in 5G NR scope with Release 17 for broadband services, and this development will likely continue in 6G networks. In parallel, Sparse Terrestrial Networks (STN) using high towers and large antenna arrays, are being developed to deliver very long transmission ranges. In this paper we discuss the characteristics and the expected performance of networks based on satellites or terrestrial large cell networks, in relation to the traffic density and required infrastructure, with a focus on remote and sparsely populated areas. The two solutions are found to deliver in complementary scenarios.